Cotton Host Plant Resistance against Spotted Bollworm, Earias vittella (Fab.) - Kanhar, Fateh Muhammad; Zubair, Hassan; Aslam, Misha; Syed, Tajwar Sultana; Jahangir, Taj Muhammad; Tunio, Saeed Ahmed; Bukero, Aslam; Panhwar, Rehana; Kanher, Khalil Ahmed; Soomro, Fakhra (Journal of Agriculture and Biology, 2025)
The seeds of three cotton lines were irradiated with gamma rays, i.e. 150, 200 and 250 Gy for phenotypic changes in plant for resistance development against spotted bollworm Earias vittella. After gamma irradiation plant Physio-morphological characters, i.e., gossypol gland density, gland size, the boll bract size and phenol concentration in floral square flowers and seeds were changed as compared to that of parents (non-irradiated) cotton lines. The field results of the parents and its gamma irradiated cotton lines in relation to resistance against E. vittella populations, the mutant line SP* (150 Gy) was found to be comparatively resistance with maximum number of gossypol density, minimum their size on bolls and higher phenol content in floral square flowers and seeds. Whereas, the mutant line SB* (250 Gy) was recorded highly susceptible to E. vittella with the lowest number of gossypol gland density, maximum their size and minimized amount of phenol concentration in floral square flowers and seeds. The phenol mixed artificial diet is a highly effective in larval growth and pupal weight loss. The gossypol density was showed non-significant and negative effects on spotted bollworm population in all parents and their gamma irradiated cotton lines. The gossypol gland size was observed non-significant and positive correlations with E. vittella in all parents and their irradiated cotton lines during 2008 and 2009, respectively. However, the bract size showed positive and significant relations, though, phenol concentrations in floral square, flowers and seeds showed non-significant and negative correlations in all parents and gamma irradiated cotton lines.
Keywords: Boll Bract; Gamma irradiation; Gossypol Gland; Resistance; Total Phenol